Age and Gender Distribution of Benign Paediatric Odontogenic Tumor: Experience of 30 Cases in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Odontogenic tumor can occur among children with the variation of different age and gender.Objective: The purpose of the present study was to see the age and gender distribution of odontogenic benigntumor originated in the oro-facial region among children.Methodology: This cross-sectional study was studied in the department of Oral and Maxillofacial Surgery at Dhaka Dental College and Hospital, Dhaka, Bangladesh from January 2010 to June 2012 for a period of 2 and half year.Children below 18 years of age irrespective of gender, histopathologically diagnosed case of odontogenic tumours were included in this study. Diagnosis of those tumour was done by history, clinical findings and histopathological or cytopathological examination. The clinical, histopathological or FNAC findings were analysed.Result: Among the total benign lesions 30 were odontogenic. In the total odontogenic tumour patients 9 cases were odontogenic keratocyst; 9 cases were ameloblastoma; 5 cases were ameloblastic fibroma; 3 cases were odontogenic myxoma and 4 cases were odontogenic fibroma.Among the patients with odontogenic tumours 15 were less than 10 years old and 15 were 10 to 18 years old. Odontogenic Keratocyst was the most common benign tumour (20.0%) cases among less than 10 years of age group. In 10 to 18 years of age group the most common reported benign tumour was Ameloblastoma (21.6%). Male and female ratio was 1.7:1. Among male Ameloblastoma was the most commonly detected benign tumour (17.1%). Among female childrenodontogenic keratocyst was the most reported tumour (18.8%).Conclusion: In conclusion the most common odontogenic benign tumour are odontogenic keratocyst and ameloblastoma.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 152-155